ANALYSIS OF IMPLEMENTATION AND REPORTING OF ENVIRONMENTAL COST ACCOUNTING AT PT. SEMENT PUGER JAYA RAYA SENTOSA - Wahyu Saskia Istiqomah; Arik Susbiyani; Elok Fitriyah (Universitas Tidar, 2021)
Environmental accounting is a practice or activity that has a role in providingaccounting information and can be influenced by the company onenvironmental problems that are realized in the form of financial and nonfinancialreports. Environmental costs are costs incurred by the company toprevent environmental damage or costs incurred in the event of environmentaldamage caused by company waste. This study aims to analyze the applicationand reporting of environmental cost accounting at PT. The Puger Jaya RayaSentosa Cement is in accordance with the current PSAK, Law, and theory.This study uses primary data obtained through observation and interviews,secondary data obtained through documentation and company record data.Data analysis techniques in this study using descriptive analysis, whichdescribes by analyzing and comparing the findings with PSAK no. 33 yearsrevised 2011 on General Mining Accounting.